DESIGN AND DEVELOPMENT OF AN IoT-BASED SNACK DRYING MACHINE FOR BALINESE TRADITIONAL SNACK (JAJE BEGINA): A CASE STUDY IN SEMPIDI VILAGE - Putrawan, Made Ari; Desnanjaya , I Gusti Made Ngurah; Putra , I Dewa Putu Gede Wiyata; Dirgayusari, Ayu Manik Dirgayusari; Ariana, Anak Agung Gede Bagus (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Jaje Begina is a traditional snack from Bali, commonly consumed and also used in ceremonial rituals. This study aims to design and develop an Internet of Things (IoT)-based drying machine, where the data collected by the dryer can be accessed through an Android application. Jaje Begina is a traditional snack often utilized during religious ceremonies. In this study, the method employed is the Research and Development (R&D) method, focusing on research and development processes with Jaje Begina as the object of study. The research results are quite satisfactory, showing that the drying process of Jaje Begina can be completed within 7 hours, whereas conventional drying methods typically require an average of two to three days. The presence of this machine is expected to significantly enhance the productivity of Jaje Begina production. In the future, this tool is anticipated to assist in improving the production process, quality, and hygiene of Jaje Begina, through the use of the designed drying machine.